2023
DOI: 10.1186/s12883-023-03127-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome after endovascular treatment for tandem occlusions: a single center retrospective analysis

Abstract: Background The endovascular treatment procedure in tandem occlusions (TO) is complex compared to single occlusion (SO) and optimal management remains uncertain. The aim of this study was to identify clinical and procedural factors that may be associated to efficacy and safety in the management of TO and compare functional outcome in TO and SO stroke patients. Methods This is a retrospective single center study of medium (MeVO) and large vessel occl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Durable patency of the carotid artery may prevent recurrent intracranial embolisms, hemodynamic insufficiency (resulting in the expansion of the ischemic cerebral territory), carotid artery restenosis or reocclusion, and the shedding of unstable plaque. 4,38,39 In addition, considering that reperfusion is an important predictor of functional outcomes in TLs, 1,40 it has been suggested that the advantage of acute CAS is most likely related to the augmentation of intracranial perfusion. 41 In our analysis, we examined acute CAS as the exposure and used successful reperfusion as the mediating factor.…”
Section: Discussionmentioning
confidence: 99%
“…Durable patency of the carotid artery may prevent recurrent intracranial embolisms, hemodynamic insufficiency (resulting in the expansion of the ischemic cerebral territory), carotid artery restenosis or reocclusion, and the shedding of unstable plaque. 4,38,39 In addition, considering that reperfusion is an important predictor of functional outcomes in TLs, 1,40 it has been suggested that the advantage of acute CAS is most likely related to the augmentation of intracranial perfusion. 41 In our analysis, we examined acute CAS as the exposure and used successful reperfusion as the mediating factor.…”
Section: Discussionmentioning
confidence: 99%